Glances on female adultery and ecclesiastical divorce in four case studies. Nueva Galicia, late 18th century - Macias Moya, Norma Aide (Huarte de San Juan. Geografía e Historia, 2023)
The ecclesiastical and civil authorities of the Old Regime imposed a female representation that conveyed acceptable behaviors. However, the challenges of the social context that women faced prevented them from complying with what was mandated. Some women chose to live in relationships such as consensual marriage, cohabitation and adultery. For the purposes of this paper we focus on adultery, which, from the Judeo-Christian conception and the law, was an attack against the family and thus the social order which, therefore, must be pointed out and punished. For this reason, it is important to explain how female adultery resulted from the disagreements originated in marital life: infidelity, abuse and lack of support. In this article, four complaints of female adultery are analyzed along with three ecclesiastical divorce suits that took place in the late eighteenth and early nineteenth centuries in the geographic space of New Galicia. In them, glimpses of the intimate life of the four women who articulate this study are revealed.
Keywords: Female adultery; infidelity; divorce; marriage; female ideal; ecclesiastical and civil courts